3D lithium ion battery fabrication via scalable stacked multilayer electrodeposition. (25th March 2019) - Synodis, Michael J; Kim, Minsoo; Allen, Mark G; Allen, Sue Ann Bidstrup
Abstract: This study focuses on the creation of 3D full cell lithium ion batteries via a multilayer stacked electrode approach. The electrodepositon based processes enable individual, deterministic control of all cell dimensions, and thus allow for tunable total energy outputs while maintaining excellent intrinsic performance. Incorporation of electrodeposited nanoporous lithium manganese oxide cathodes and thin film nickel–tin anodes into a vertically interdigitated multilayer cell enables energy densities of up to 193 Wh l −1 and power densities of up to 1233 W l −1 . Additionally, the multilayer fabrication increases device areal and volume scalability over multiple orders of magnitude, resulting in total energy outputs of up to 20 mWh and power outputs of 178 mW.